Preliminary Conceptual design of FCC-hh cryoplants: Linde evaluation. (April 2019) - Millet, F; Tavian, L; Cardella, U; Amstutz, O; Selva, P; Kuendig, A
Abstract: In the framework of an international collaboration, a 100 TeV hadron collider in a 100-km long tunnel is under study as a future circular collider beyond LHC at CERN. Its design is based on 16-T superconducting magnets cooled at 1.9 K by 10 cryoplants with a unit equivalent capacity of 100 kW at 4.5 K, up to 4 times larger than the present state-of-the-art. Half of the entropic refrigeration load is due to the synchrotron radiation produced by the high-energy proton beams and deposited on beam screens cooled between 40 and 60 K. This non-conventional thermal load distribution is an additional challenge for the cryogenic system. An engineering study on FCC-hh cryoplants is in progress with world-leader industries to define the preliminary conceptual design of industrial solutions and to confirm innovative technologies. The paper recalls the FCC-hh cryogenic requirements, presents the main results of Linde Kryotechnik study and highlights some identified R&D efforts.